2019
DOI: 10.3389/fphar.2019.00844
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine for Coronary Heart Disease: Clinical Evidence and Possible Mechanisms

Abstract: Coronary heart disease (CHD) remains a major cause of mortality with a huge economic burden on healthcare worldwide. Here, we conducted a systematic review to investigate the efficacy and safety of Chinese herbal medicine (CHM) for CHD based on high-quality randomized controlled trials (RCTs) and summarized its possible mechanisms according to animal-based researches. 27 eligible studies were identified in eight database searches from inception to June 2018. The methodological quality was assessed using seven-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 103 publications
0
26
0
Order By: Relevance
“…TCM has been used, for more than 2,000 years, to treat cardiovascular diseases as well as for prevention and treatment of myocardial infarction diseases [ 49 ]. Currently, TCM is increasingly becoming a popular alternative or complementary medicine across many countries due to the urgent need for multitarget, multipathway, and personalized treatment [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…TCM has been used, for more than 2,000 years, to treat cardiovascular diseases as well as for prevention and treatment of myocardial infarction diseases [ 49 ]. Currently, TCM is increasingly becoming a popular alternative or complementary medicine across many countries due to the urgent need for multitarget, multipathway, and personalized treatment [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…e therapeutic effect of Chinese traditional medicines for treating CHD is not bad and even stronger than some western medicines, and Chinese traditional medicines are characterized by little toxicity and side effect. erefore, the application prospect of Chinese traditional medicines in CHD is great [47]. Along with the development of modern pharmaceutical technologies, oral preparations and injections for the prevention and treatment of CHD based on classical TCM prescriptions or theories have sprung up in large numbers [48].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%
“…More recently, traditional Chinese medicine has received great attention because it has a variety of ingredients, can act on multiple targets and pathways and plays an overall regulatory role (Hu et al, 2019). Recent studies have confirmed that compared to Western medicine, TCM has fewer side effects and unique advantages for treating CHD (Zhang et al, 2019;Leung and Xu, 2020). Therefore, the exploration of the pharmacological mechanisms of TCM may provide insights into the development of new drugs.…”
Section: Introductionmentioning
confidence: 99%